TRABAJO INFORMAL Y ECONOMÍA INFORMAL EN MÉXICO. UN ACERCAMIENTO TEÓRICO - Juan Carlos Velázquez Torres; Luis Roberto Domínguez Aguirre (European Scientific Journal, ESJ, 2015)
This article aims to show the results of the review of relevant literature of informal work and the informal economy in Mexico between 2002 and 2010. The method used to evaluate the literature was based on the seven steps for synthesis research: problem formulation, literature search, obtaining information, assessing the quality of studies, analysis and integration of results, interpretation of evidence and presentation of results. Were evaluated eleven different national and international studies of government and educational institutions. The findings suggest that the informal economy is of varied elements that make it a complex problem, whose recent emergence as a social and economic problem has caused the attention of the sectors involved.